THE ROLE OF THE FIRST 1000 DAYS OF LIFE (1000 HPK) IN STUNTING PREVENTION TO REALIZE A HEALTHY AND INTELLIGENT GENERATION IN THE PONDOK PESANTREN ENVIRONMENT - Wiwik Winarningsih; Muhammad Fifin Kombih; Marselli Widya Lestari; Hawin Izza Nirmala; Nanda Nabilah Putri; Fajriatush Sholahah; Shafira Cahyani Rakhmawati; Naila Irtabaza Rosyida; Nafil Akmal Mahrus; Retno Diah Putri Ekayanti (Institute for Research and Community Service, Health Polytechnic of Kerta Cendekia, Sidoarjo, 2026)
Stunting remains an unresolved health problem in Indonesia. The most appropriate period to meet a child's nutritional needs is during the First 1000 Days of Life (1000 HPK), from conception until the child is two years old. Initial surveys of female students at Pondok Pesantren Al Fitrah As Salafiyah indicated a low understanding of preparation for the 1000 HPK, necessitating health education. This community service activity aims to increase the knowledge and role of students regarding the 1000 HPK and balanced nutrition for preparation and during a healthy pregnancy. The methods used include counseling on stunting and the 1000 HPK, training in the form of balanced nutrition education, and demonstrations of preparing nutritious menus. Evaluation was conducted through pre-test and post-test to measure the increase in knowledge, as well as observation of the students' participation in discussions and practices. The results show a significant increase in knowledge of 81.1% based on the comparison of pre-test and post-test scores. Furthermore, the students showed high enthusiasm, reflected in their active participation in discussions and direct practice. In conclusion, the counseling and training were effective in increasing students' knowledge about the 1000 HPK and stunting prevention. The active involvement of pesantren adolescents shows great potential as health education agents. It is recommended that similar activities be carried out regularly and integrated into pesantren programs to strengthen the community's role in stunting prevention.